The impact of energy consumption on economic growth: application of CES function for Romania - Niță, Dorina; Stoicuța, Nadia (Journal of Business Economics and Management, 2025)
This paper analyses the contribution of the renewable and non-renewable primary energy consumption per capita and the gross fixed capital formation per capita to sustainable economic growth using two models approximated by CES-type functions. Estimates are made by applying the TRANSLOG method. The results obtained following the analysis of data over a period of 33 years (1990–2022), show that only the increase in gross fixed capital formation per capita contributes to the economic growth. The increase of the consumption of renewable primary energy per capita, respectively of non-renewable primary energy leads to decreases of real GDP per capita. The Granger causality test, reflects that only non-renewable primary energy consumption per capita has a unidirectional causality relation with real GDP per capita. Also, the technical efficiency of inputs in relation to GDP, analysed through an SFA model, suggests that, in general, the resources are used efficiently in the case of Romania. The current inability of renewable primary energy consumption to generate increases in real GDP per capita can be an aspect for policymakers to consider in their efforts to adapt successful low-carbon energy transition models to national needs, so that renewable energy becomes a determinant with a positive and substantial influence on economic growth.